Tinjauan Hukum Terhadap Tindak Pidana Perdagangan Orang di Indonesia (Studi Kasus Putusan Nomor 60/Pid.Sus/2020/PN.Cjr) - Ray, Keysha Gordiola Zahra; Hamonangan, August (PT Elaborium Elevasi Indonesia, 2025)
Human trafficking is one of the crimes that is currently rampant in Indonesia, which is carried out in an organized manner by an individual or group of people with the aim of exploiting someone either economically or sexually. Based on data obtained by SIMFONI PPA, there were 678 victims of human trafficking in 2021. The problems that will be studied are how the criminal law policy is towards human trafficking, what are the factors causing human trafficking and to what extent law enforcement is against human trafficking cases based on a case study of decision Number 60/Pid.Sus/2020/PN.Cjr. The research method used is normative juridical which is descriptive analytical in nature. Law Number 21 of 2007 concerning the Eradication of Human Trafficking is a product of criminal law policy formed by the government. The form of legal protection that can be obtained by victims of criminal acts can be in the form of restitution rights, rehabilitation, and confidentiality of identity. This study is expected to provide recommendations for improving law enforcement policies and practices in eradicating TPPO in Indonesia.